(untitled) (Research, Society and Development, 2025)
Currently, different brands of wind turbines are in operation in Brazil, and the use of more efficient technologies results in higher capacity factors, which consequently generate greater amounts of energy and reduce environmental impacts. In this sense, this study aims to estimate the energy impacts of the use of large-scale wind turbines by comparing and analyzing the power x speed curves and the capacity factors of three large-scale wind turbines studied. The case study was carried out for the climatic conditions of the city of Itapipoca - CE, since the city has great potential for wind generation. With the case study, it was possible to verify that there was a difference of more than 7% in the capacity factors between the most efficient and the least efficient technology, of the three studied. Thus, the work concludes that the choice of a more efficient generator can result in significant amounts of additional energy generated, resulting in a reduction of greenhouse emissions, since wind generation is one of the least polluting.